Nutrition Education Intervention Via Instagram among Adolescents: A Scoping Review - Simatupang, Abdul Malik; Dewi, Yulia Lanti Retno; Andayani, Tri Rejeki (Global Health Science Group, 2024)
Adolescence is a phase of rapid and critical development, necessitating increased energy, protein, vitamin and mineral requirements. However, poor dietary patterns during adolescence pose a risk factor for malnutrition, negatively impacting health into adulthood and, requiring nutritional interventions to break the cycle intergenerational malnutrition. Social media-based nutritional interventions through instagram have the potential to provide health information for adolescents. Objective: This study aimed to evaluate the development stages of intervention media and the effectiveness of nutritional education interventions through instagram addressing adolescent nutritional issues. Method: The study follows Arksey and O'Malley framework with PRISMA-ScR systematic review method. Article searches were conducted on Google, Scopus, Science Direct, PubMed and Google Scholar databases using keywords